(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article discusses the features of forming the concept of a “physical field” in school physics education. The concept of a physical field is one of the key ideas in the physics curriculum, but its abstract nature presents certain difficulties for students. The article emphasizes the importance of gradual and accessible explanations, the use of visual aids, analogies, and simple experiments. Special attention is given to teaching methods that help students consciously understand a physical field as a form of matter that transmits interaction at a distance. It is concluded that effective formation of this concept requires a combination of theory and practice, as well as consideration of the age and psychological characteristics of schoolchildren.